Generation Maintenance Scheduling Considering Carbon Tax and Social Cost - Prukpanit, Panit; Prapurt, Nuttapong (2024 12th International Electrical Engineering Congress (iEECON), 2024)
In power systems, generation maintenance scheduling (GMS) is operated to prolong life span of generation units (GUs) to increase the system reliability. Nonetheless, environmental concerns have been widely considered, leading to the social cost and carbon tax policies enforced in several countries. By considering these issues, this paper proposes multi-objective GMS models to minimize the GMS costs incurred by operation and maintenance, social impact, and carbon tax. The models are solved based on the lexicographic method. The GSM algorithm in the published work is also run to demonstrate the robustness of the results. A numerical example is implemented on the IEEE 24-bus test system. The outcomes suggest that the proposed GMS algorithms outperform previous work in terms of financial cost, carbon generation, and system reliability for a generation company.